A Modified Dual Input DC-DC Converter for Hybrid Energy Application - Sivaprasad Athikkal; Kumaravel Sundaramoorthy; Ashok Sankar (Institute of Advanced Engineering and Science, 2017)
Power electronic interface has reached a new level in the area of hybrid energy integration nowadays. The existence for the concept of hybrid energy integration is truly questionable without a proper power electronic interface. In this paper, a modified dual input DC-DC converter which is capable of incorporating two distinct V-I characteristic sources such as solar-PV, battery, fuel cell, etc., is proposed. The converter has the ability to operate in both unidirectional and bidirectional mode with buck, buck-boost and boost operation. The software simulation of the proposed converter has been conducted in MATLAB/Simulink platform in a detailed manner and an experimental prototype of the propsed converter has been built to validate the simulation results.